FULL STACK QUARKUS AND REACT hands-on full stack web development with Java, React, and Kubernetes - San Felix, Marc Nuri (PACKT PUBLISHING LIMITED, 2023)
Create and deploy standalone, fully functional, web applications using Quarkus and React Key Features Get up and running with web application development speedily using React and Quarkus Get an overview of how to make a Java backend work seamlessly with a JavaScript frontend Learn how to deploy your working application to Kubernetes and share it with the world Book Description React has established itself as one of the most popular and widely adopted frameworks thanks to its simple yet scalable app development abilities. Quarkus comes across as a fantastic alternative for backend development by boosting developer productivity with features such as pre-built integrations, application services, and more that bring a new, revolutionary developer experience to Java. To make the best use of both, this hands-on guide will help you get started with Quarkus and React to create and deploy an end-to-end web application. This book is divided into three parts. In the first part, you'll begin with an introduction to Quarkus and its features, learning how to bootstrap a Quarkus project from the ground up to create a tested and secure HTTP server for your backend. The second part focuses on the frontend, showing you how to create a React project from scratch to build the application's user interface and integrate it with the Quarkus backend. The last part guides you through creating cluster configuration manifests and deploying them to Kubernetes as well as other alternatives, such as Fly.io. By the end of this full stack development book, you'll be confident in your skills to combine the robustness of both frameworks to create and deploy standalone, fully functional web applications. What you will learn Create a Quarkus project from scratch to gain a basic understanding of its advantages Create a persistence layer in a Quarkus application Secure your application by adding authentication and authorization features Use Quarkus Dev services to implement integration tests with real-world databases Start creating a React project from scratch Use React Testing Library to test React components Identify the most suitable alternatives for deploying your application to the cloud Who this book is for This book is for backend web developers who have at least basic experience with Java and would like to learn React to build full stack apps by integrating it with a Quarkus-based backend. Frontend web developers with basic JavaScript experience will also find this book useful to learn how to implement a backend in Quarkus and integrate it with their frontend to create full stack web applications. Beginner-level knowledge of Java and JavaScript is recommended, but any developer experienced either with Java or JavaScript should be able to follow the backend and frontend parts easily.